Evaluation of procera/porcelain interface in metal-free prosthesis - Yasuda, S. H. [UNESP]; Guastaldi, A. C. [UNESP]; Vedovato, E. (Trans Tech Publications, 2005)
Prosthetic substructures for dental application are veneered by porcelain comprising a structure with different elastic modulus and thermal expansion coefficients layers. This structure may present residual stresses in different layers leading to crack propagation and delamination. Although veneering porcelain remains basically on same strength than standard feldspathic porcelains, new ceramic cores have been developed with higher mechanical properties overcoming metal substructures, improving esthetics and biocompatibility. The interface between the Procera dense sintered alumina core and the manufacturer recommended veneering porcelain (AllCeram-Degussa) were evaluated using SEM in coping shaped specimen simulating the standard dental preparation. There were neither crack presences at the interface nor porcelain delamination.
Keywords: Biomaterials; Interface; Metal-free; Porcelain; Procera; Crack propagation; Elastic moduli; Scanning electron microscopy; Interfaces (materials)